VPS26C homozygous nonsense variant in two cousins with neurodevelopmental deficits, growth failure, skeletal abnormalities, and distinctive facial features. Issue 4 (26th December 2019) - Beetz, Christian; Ameziane, Najim; Kdissa, Ameni; Karageorgou, Vasiliki; Bauer, Peter; Suleiman, Jehan; Sutton, V. Reid; El‐Hattab, Ayman W.
Abstract: In this report, we describe two cousins with cognitive impairment, growth failure, skeletal abnormalities, and distinctive facial features. Genome sequencing failed to identify variants in known disease‐associated genes explaining the phenotype. Extended comprehensive analysis of the two affected cousins' genomes, however, revealed that both share the homozygous nonsense variant c.178G>T (p.Glu60*) in the VPS26C gene. This gene encodes VPS26C, a member of the retriever integral membrane protein recycling pathway. The potential vital biological role of VPS26C, the nature of the variant which is predicted to result in loss‐of‐function, expression studies revealing significant reduction in the mutant transcript, and the co‐segregation of the homozygous variant with the phenotype in two affected individuals all support that VPS26C is a novel gene associated with a previously unrecognized syndrome characterized by neurodevelopmental deficits, growth failure, skeletal abnormalities, and distinctive facial features. Abstract :